Peningkatan Pengetahuan dan Sikap Siswa terhadap Pengamalan Nilai-Nilai Pancasila Komunitas Rohani Islam Melalui Workshop - Pratama, Dinar; Musa, Musa (Universitas Negeri Malang, 2020)
This study aimed to determine the increase in knowledge and attitudes towards practicing the values of the Pancasila by Islamic spiritual community of State Vocational Schools in the City of Pangkalpinang through workshops. The approach in this study was quantitative with an experimental method. The design used pre-experimental design one group pre-test post-test. The mean score of knowledge of Pancasila values was 69.70 in the pre-test and 75.3 in the post-test, there was an increase in students’ knowledge after attending the workshop which descriptively increased by 8%. The average score of students’ attitudes toward practicing Pancasila values in the pre-test was 3.81 and the post-test was 4.00, there was a significant increase in the attitude scores of students towards the practice of Pancasila values after attending workshops which descriptively increased by 3%. The students’ knowledge and attitudes towards practicing the values of Pancasila increased through workshop.